Eleven new species of the Homoneura (Homoneura) beckeri group from Yunnan, China (Diptera, Lauxaniidae) - Li, Wenliang; Yang, Ding (Zootaxa, 2012)
In the Homoneura (Homoneura) beckeri group, the following eleven species from Yunnan, China are described as new to science: H. (H.) baihualingensis sp. nov., H. (H.) brevituba sp. nov., H. (H.) conica sp. nov., H. (H.) cornis sp. nov., H. (H.) dulongjiangica sp. nov., H. (H.) ensata sp. nov., H. (H.) gemmiformis sp. nov., H. (H.) latizona sp. nov., H. (H.) longiprocessa sp. nov., H. (H.) pilifera sp. nov. and H. (H.) trilineata sp. nov.. A key to the species of the H. (H.) beckeri group in the Oriental Region is presented.